The effects of firm-specific factors on the profitability of non-life insurance companies in Turkey - Emine Öner Kaya (International Journal of Financial Studies, 2015)
This study investigates the firm-specific factors affecting the profitability of non-life insurance companies operating in Turkey. For this purpose, data of 24 non-life insurance companies operating in Turkey from the period 2006-2013 were brought together to obtain 192 observed panel data sets. In this study, profitability is measured by two different variables: technical profitability ratio and sales profitability ratio. According to the empirical results, the firm-specific factors affecting the profitability of Turkish non-life insurance companies are the size of the company, age of the company, loss ratio, current ratio, and premium growth rate.
Keywords: C23; G22; 330; profitability; firm-specific factors; non-life insurance companies; Turkey